ifo World Economic Survey November 2017 - Dorine Boumans; Tobias Schuler; Christoph Zeiner (ifo World Economic Survey, 2017)
World Economic Climate: ifo World Economic Climate Indicator Reaches Highest Level Since 2011 - Advanced Economies: Climate in Advanced Economies Remains Favourable - Emerging and Developing Economies: Emerging and Developing Economies Expect Recovery to Remain on Track - Heatmap: Visualisation of WES Results as a Heat Map - New Indicator: International Trade Volume and its Expectations in Selected Aggregates - Special Topic: A Year After the Election: Trump's Impact on the Economy
Keywords: 330